False Beliefs About Asylum Seekers to Australia: The Role of Confidence in Such Beliefs, Prejudice, and the Third Person Effect - Pedersen, A.; Hartley, Lisa (Cambridge University Press, 2017)
There has been much controversy about the treatment of asylum seekers in Australia in recent years, with the Australian Government continuing to enforce a very hard-line stance on asylum seekers who arrive to Australia by boat. The present study examined attitudes towards asylum seekers using 164 Australian community members during June 2015 by way of questionnaire. Our primary research question involved how five variables predicted false beliefs about asylum seekers. Specifically, we measured prejudice, the third-person effect, and confidence in the answers given to false beliefs about asylum seekers. Regression results indicated that the main predictors of false beliefs were right-wing political orientation, prejudice, confidence in espousing false beliefs, and the third-person effect (politicians). Furthermore, most of our community participants accepted a large number of false beliefs as being true, with approximately two-thirds of our participants scoring above the midpoint. This reflects similar findings over the last decade or so. Our results indicate that, if one believes in bottom-up change, a more nuanced approach needs to be undertaken with community anti-prejudice interventions.